Umma and the Nation-State: Dilemmas in Refuge Ethics - Mohammed Hossameldeen (17307647) (2022)
This article addresses the question of the Muslim umma (the universal community of Muslims) which arises within the context of the ongoing debates about the status of refugees and their rights around the world, especially in the Muslim world, where a significant majority of migrants and refugees originate and are hosted. We question the existence of the Muslim umma under contemporary circumstances and discuss the extent to which the modern nation-state has undermined the principles of Muslim unity and solidarity beyond national borders. We also examine how Islamic ethics and law (fiqh) identify the imperatives of providing comfort and protection for refugees (whether they are Muslim or non-Muslim) individuals, groups, and communities when required or requested. We see this in principle, but not always in practice. Are refugee policies applied by Muslim-majority countries today in accordance with the fundamental Islamic teachings and experiences of the original hijra? Or have such principles been made redundant by the political-geographic imperatives of ethnicized nation-states? To what extent can applied policies in Muslim-majority countries be developed and enhanced in the light of umma principles that might alleviate the longstanding refugee crises in this troubled area of the world? The article consists of three main sections. The first provides a theoretical and religious analysis of the idea of the umma as an inclusive entity that encompasses all Muslims, contrasted with the modern nation-state as an exclusive geographically defined political institution. The second looks at three Muslim-majority countries that played a significant hosting role in refugee crises over the past decade, namely Jordan, Bangladesh, and Turkey. We offer some insight in understanding to what extent their policies or behavior were based upon ummatic principles, or secularist notions of national interest and humanitarian aid? The last section summarizes the recent innovation providing for Muslim refugees through a UNHCR arrangement and adaptation with the Islamic charitable obligation of Zakat. It is suggested that the UNHCR Zakat Fund is an ummatic manifestation that has already proved honorable and viable. The conclusion calls for a better understanding of the umma as it is in the Islamic consciousness towards an effective reforming of refugee policies and practices, suggesting a further enhancement of ummatic institutional collaboration between the OIC and UNHCR for refugee integration. Other Information Published in: Journal of International Humanitarian Action License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://doi.org/10.1186/s41018-022-00124-z